Ambient PM10 and Respirable Dust Levels Near Gold Mine Tailings Storage Facilities in South Africa. Issue 2 (4th January 2019) - Andraos, Charlene; Dekker, Kobus; Gulumian, Mary
Abstract : Gold mine tailings storage facilities (TSFs) contribute largely to high dust levels in the Gauteng and North‐West provinces, South Africa, and are seen as a public health concern. Currently, the South African National Ambient Air Quality Standard for PM10 is 75 μg m −3 (24 h) and no limits have yet been set for respirable PM4 levels. This study investigates the ambient PM10 levels close to three TSFs as well as respirable PM4 levels of school learners at various distances from five TSFs during the dry and wet season. The results show that the ambient PM10 levels exceeded the current limit to a large degree between three and five times during the sampling period at the three TSFs studied. Analysis of wind speed, direction, and frequency show that emissions from two of the three TSFs could have been a possible dust source contributing to some of these exceedances. The respirable PM4 levels ranged from 10–130 μg m −3 (wet season) to 3–173 μg m −3 (dry season). For two TSFs studied, sampling sites close to the TSFs showed significantly higher PM4 levels compared to those further away, which was, however, likely not the result of TSF emissions but rather from other dust‐generating sources. Overall, these results reveal high PM10 levels in surrounding communities, which should be monitored and investigated further. Abstract : Dust exposure to communities surrounding gold mine tailings storage facilities (TSFs) in South Africa is assessed in this study. In certain instances, the results show high dust events in residential areas during which emissions from TSFs have contributed to the dust overload. These results should be monitored and investigated further and serve as a starting point for future sampling campaigns.